Frequency of Cardiac Autonomic Neuropathy and its Various Grades in Type 2 Diabetes Mellitus - Furhaj Mueen Siddique, Imran Ahmed Moinuddin, Maida Nazir, Muhammad Kashif, Muhammad Mubeen Akhtar, Asma Jabeen (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Cardiovascular autonomic neuropathy (CAN) is a common and one of the major complication of diabetes mellitus. It is also the most under diagnosed and least understood diabetic complication4. Objective: To determine the frequency of cardiac autonomic neuropathy and its various grades in type 2 diabetes mellitus. Study Design: Cross Sectional Study. Setting: Medical OPD as well as from diabetic clinic of Services Hospital, Lahore. Methodology: Total 195 patients of either sex or age between 18 to 60 with at least 10 years duration of type 2 Diabetes Mellitus were enrolled. Cardiac Autonomic Neuropathy was determined using Ewing’s criteria. Frequency of CAN and its severity grades was recorded. Result: Mean age of sampled population was 54.42 ± 2.925 ranged from 44 to 60 years. There were 77 (39.5%) female and 118(60.5%) patients (60.5%) were male. Out of 195, 99 (50.8%) patients had cardiac autonomic neuropathy, 34 (17.4%) patients had early, 56 (28.7%) had definite, 8 (4.1%) had severe & 1 patient had atypical cardiac autonomic neuropathy. It was associated with advancing age but gender and duration of diabetes had no effect. Conclusion: The study concludes that frequency of cardiac autonomic neuropathy is quite high (50.8%) in patients with more than ten years duration of type II diabetes. Thirty four (17.4%) had early level, 56 patients (28.7%) had definite, 8 patients (4.1%) had severe and 1 patient had Atypical cardiac autonomic neuropathy. Keywords: Cardiac Autonomic Neuropathy, Diabetes, Insulin resistance, Autonomic instability, Neuropathy